Pengaruh Latihan Knee Tuck Jump Terhadap Kemampuan Lompat Jauh - Muhammad Zaenal Arwih (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine whether there is an effect of knee tuck jump training on long jump ability. This study used experimental research, using a pre-test and post-test one-group design. The research sample consisted of 32 students. The instrument used in this study was the extended jump ability test. Data analysis techniques used descriptive analysis to find out the average, normality test, homogeneity of the pre-test and post-test, and hypothesis testing with t-test statistics. Based on the results of the study, it can be concluded that the t-test with a significance level of 0.05 indicates tcount = 5.00 > ttable = 2.039. This result means a difference in the long jump results between the pre-test and post-test in students after doing the knee tuck jump exercise. In conclusion, there is an effect of knee tuck jump training on long jump ability. Keywords: Exercise, Knee Tuck Jump, Long Jump.